Pengaruh Distribusi, Kelangkaan, dan Aplikasi Pangkalan terhadap Keputusan Pembelian LPG 3Kg di PT Agung Cipta Sentosa Berdikari - Tri Octaviani; Hendri Sucipto; Nur Aisyah; Dumadi Dumadi; Nurkojin Nurkojin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of distribution, scarcity, and the use of merchant base applications on the purchasing decisions of 3kg LPG gas customers at PT Agung Cipta Sentosa Berdikari. The background of this study is based on the importance of sustainable household energy supplies, especially 3kg LPG, which is a basic need for the community. Uneven distribution, the issue of scarcity, and the less than optimal use of digital technology by bases are challenges that need to be reviewed from a consumer behavior perspective. The research subjects were active customers who purchased 3kg LPG at the company. Sampling was determined using the Slovin formula with a margin of error of 10% from a population of 359 customers, resulting in 78 respondents. Data collection techniques were carried out through observation, interviews, documentation, and the distribution of structured questionnaires. The research instrument was tested through validity and reliability tests which showed that all questionnaire items met the requirements for reliability and validity. Classical assumption tests such as normality, linearity, and multicollinearity were also conducted and showed that the data were suitable for analysis using multiple linear regression. The results of the study indicate that distribution, scarcity, and the use of merchant base applications simultaneously and partially have a positive and significant effect on the purchase decision of 3kg LPG. Timely and equitable distribution increases customer trust. Scarcity creates a perception of urgent need that encourages purchases. Meanwhile, the use of merchant base applications provides easy access to information and price transparency, thereby increasing customer convenience in transactions. The implications of this study's results demonstrate the importance of an efficient distribution strategy, good stock management to avoid shortages, and digitalization of services through merchant base applications to support consumer decisions.